Circadian variations in pathogenesis of ST-segment elevation myocardial infarction. (25th November 2020) - Araki, M; Yonetsu, T; Kurihara, O; Nakajima, A; Lee, H; Soeda, T; Minami, Y; Yan, B.P; Adriaenssens, T; Boeder, N.F; Nef, H.M; Kim, C.J; et al.
Abstract: Background: Previous studies have reported a circadian variation in the onset of ST-segment elevation myocardial infarction (STEMI). However, underlying mechanisms for the circadian variation have not been fully elucidated. Purpose: We investigated the relationship between onset of STEMI and the underlying pathology using optical coherence tomography (OCT). Methods: Patients presenting with STEMI were selected from an international, multi-center, longitudinal registry study, which included patients who underwent OCT imaging of the culprit lesion at 11 institutions in 6 countries. Onset of MI was estimated using the time of OCT imaging. Patients were divided into 4 groups based on the estimated time of onset (00:00–05:59, 06:00–11:59, 12:00–17:59, or 18:00–23:59). Underlying pathologies of MI (plaque rupture, plaque erosion, and calcified plaque) were compared among the 4 groups. Results: Among 648 patients, plaque rupture was diagnosed in 386 patients (59.6%), plaque erosion in 197 patients (30.4%), and calcified plaque in 65 patients (10.0%). A marked circadian variation was detected in the incidence of plaque rupture with a peak at 9:00, whereas it was not evident in plaque erosion or calcified plaque. The probability of plaque rupture increased in the periods of 06:00–11:59 (odds ratio: 2.13, 95% confidence interval: 1.30 to 3.49, p=0.002) and 12:00–17:59 (odds ratio: 2.10, 95% confidence interval: 1.23 to 3.58, p=0.005), compared to the period of 00:00–05:59. This circadian pattern was observed only during weekdays (p=0.013) and it was not evident during the weekend (p=0.742). Conclusions: Plaque rupture occurred most frequently in the morning and the circadian variation was evident only during the weekdays. Acute MI caused by plaque rupture may be related to catecholamine surge. Funding Acknowledgement: Type of funding source: None